The impact of patient-generated contextual data on communication in clinical practice: A qualitative assessment of patient and clinician perspectives. Issue 4 (April 2020) - Cusatis, Rachel; Holt, Jeana M.; Williams, Joni; Nukuna, Sandile; Asan, Onur; Flynn, Kathryn E.; Neuner, Joan; Moore, Jennifer; Makoul, Gregory; Crotty, Bradley H.
Highlights: Patient contextual data (PCD) fostered rapport among patients and healthcare team. The PCD tool enabled patient/provider communication outside the clinic visit. Participants recognized the PCD tool offered space to communicate sensitive topics. Recording and reviewing PCD ahead of visit better prepares patients and providers. Abstract: Background: Effective communication is integral to patient-centered care, yet external pressures can impede the ability to discuss important topics. One strategy to facilitate communication is pre-visit collection and sharing of patient contextual data (PCD), including life circumstances such as their beliefs, needs, and concerns. Objective: To understand how patients and care team members perceive the electronic collection of PCD and its impact on communication in the context of a large academic health system that implemented PatientWisdom, a new technology that elicits PCD from patients and integrates within the electronic health record (EHR). Methods: We conducted focus groups with patients (n = 26) and semi-structured interviews with primary care team members (n = 20). Qualitative analysis of focus group/interviews included an iterative and reflexive inductive technique to uncover emergent themes. Results: Four themes were reflected among both patient and care team: (1) the technology enhances the patient's voice; (2) the technology creates a safe space for patients to share sensitive topics; (3) PCD facilitates rapport not only between patient and provider but the entire care team; (4) PCD aligns patient and clinician goals. Two unique themes emerged among patients: (1) PCD provides opportunity for reflection; (2) PCD humanizes patients in the clinical context. One theme was evident in provider comments: collecting PCD may potentially undermine trust if not reviewed by clinical teams. Conclusion: PCD collected directly from patients and available within the EHR was seen by patients and care team members as beneficial to communication. PCD collection supports a paradigm shift towards coproduction of health information and a shared responsibility for information gathering but requires investment from patients and care team to ensure the data are effectively utilized. Practice value: PCD may be useful for team-based care, enabling physicians and non-physician staff to more quickly and responsively connect with patients.